Does Growth Generate Jobs in Eastern Europe and Central Asia? - Richter, Kaspar; Witkowski, Bartosz (World Bank, Washington, DC, 2014)
In Eastern Europe and Central Asia, the link from growth to jobs was tenuous in the first decade of the transition, giving rise to the notion of jobless growth. Yet, European countries suffered large job losses during the recent recession, suggesting that jobs and growth are closely entwined. This study takes a new look at this issue. It provides a cross-country analysis of the employment intensity of growth over the last decade and a half in Eastern Europe and Central Asia, which includes the 11 Central and Eastern European countries that joined the EU since 2004, the countries of former Yugoslavia, the Countries of Independent States and Turkey. The authors compare these findings with other regions in the world. The paper shows that the responsiveness of employment to output increased in the second decade of the transition. It also finds that in some instances employment growth increases with reforms of labor and product markets, stronger macroeconomic policy frameworks, better governance, and more economic integration and diversification.